2014
DOI: 10.3928/00220124-20140122-01
|View full text |Cite
|
Sign up to set email alerts
|

Newly Qualified South African Nurses’ Lived Experience of the Transition From Student to Community Service Nurse: A Phenomenological Study

Abstract: Preparation for the role transition from student nurse to graduate community service nurse requires a 4-year structured program that includes training in conflict management, assertiveness, and practical ethics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…) and/or focus groups (Ellis & Chater , Roziers et al. ). Studies, including literature reviews varied in sample sizes (range 2–35) participants/articles.…”
Section: Resultsmentioning
confidence: 99%
“…) and/or focus groups (Ellis & Chater , Roziers et al. ). Studies, including literature reviews varied in sample sizes (range 2–35) participants/articles.…”
Section: Resultsmentioning
confidence: 99%
“…The limited studies on the experiences of nurses performing CCS in South Africa since 2008 have been entirely qualitative in nature, focusing on the experiences and support offered to university graduates during this period. Roziers, Kyriacos and Ramugondo ( 2014 ) explored Cape Town university graduates’ experiences before and after CCS and found that these nurses’ experience of the realities of practice made them fearful and anxious, whilst Thopola, Kgole and Mamogobo ( 2013 ) found that Limpopo graduates’ professional development was challenged by staff shortages and a lack of resources. Two studies were conducted in Gauteng: Du Plessis and Seekoe ( 2013 ) investigated university graduates’ experience of midwifery and the respondents identified the complexities of practice and ambiguous situations as challenges; Tsotetsi ( 2012 ) found that the newly-qualified nurses had difficulty in adapting to the work environment because of limited support, verbal abuse, role conflict and unexpected workloads.…”
Section: Introductionmentioning
confidence: 99%
“…Well-structured orientation programme (Beyers 2013; Govender et al 2017; Nkoane 2015; Roziers et al 2014; Shezi 2014; Tsotetsi 2013; Zaayman 2016).…”
Section: The Review Methodsmentioning
confidence: 99%